2015
DOI: 10.3389/fimmu.2015.00244
|View full text |Cite
|
Sign up to set email alerts
|

Successive Oral Immunizations Against Piscirickettsia Salmonis and Infectious Salmon Anemia Virus are Required to Maintain a Long-Term Protection in Farmed Salmonids

Abstract: Currently, there is a growing demand to determine the protective status of vaccinated fish in order to prevent diseases outbreaks. A set of different parameters that include the infectious and immunological status of vaccinated salmonids from 622 Chilean farms were analyzed during 2011–2014. The aim of this study was to optimize the vaccination program of these centers through the determination of the protective state of vaccinated fish using oral immunizations. This state was determined from the association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…The underlying mechanisms were not studied and are not known in detail but could be due to pathogen exposure and antibody consumption, as has been seen in IPN-vaccinated salmon (57). In line with such a thinking, the authors showed that declining levels of anti- P. salmonis antibodies coincide with increase in SRS-related mortality (34) indicating that pathogen exposure at least partly explained antibody consumption. Further, oral revaccination increased the circulating antibodies to levels equivalent to or higher than what was achieved from the primary injection vaccine (34), and even more pronounced when a second oral boost was administered (Figure 5).…”
Section: Translating Knowledge Of Host–pathogen Interactions Into Optmentioning
confidence: 66%
See 4 more Smart Citations
“…The underlying mechanisms were not studied and are not known in detail but could be due to pathogen exposure and antibody consumption, as has been seen in IPN-vaccinated salmon (57). In line with such a thinking, the authors showed that declining levels of anti- P. salmonis antibodies coincide with increase in SRS-related mortality (34) indicating that pathogen exposure at least partly explained antibody consumption. Further, oral revaccination increased the circulating antibodies to levels equivalent to or higher than what was achieved from the primary injection vaccine (34), and even more pronounced when a second oral boost was administered (Figure 5).…”
Section: Translating Knowledge Of Host–pathogen Interactions Into Optmentioning
confidence: 66%
“…However, reduced sensitivity and increased resistance to penicillin, streptomycin, oxolinic acid, and oxytetracycline have been reported (12). There are commercial vaccines for intraperitoneal injection available, but these have shown variable results (34). Vaccinated fish come down with SRS toward the end of the production cycle which causes severe economic losses, i.e., death of fish close to harvest.…”
Section: Disease Preventionmentioning
confidence: 99%
See 3 more Smart Citations